Characterization of Native and Graft Copolymerized Albizia Gums and Their Application as a Flocculant. (18th June 2017) - Afolabi, T. Adeniyi; Adekanmi, Daniel G.
Abstract : The functional properties and flocculation efficiency of purified Albizia saman (AS) and Albizia glaberrima (AG) gum exudates modified by graft copolymerization with acrylamide were investigated. The grafting efficiency of AS and AG was 54 and 58%, respectively. The cold water-insoluble gel of native AS and AG was 38.23 and 35.55%, which increased to 39.75 and 40.55% after graft copolymerization. Graft copolymerization of AS and AG gums reduced their oil binding and emulsion capacity from 4.89 and 3.44% to 3.69 and 2.40%, respectively. The dissolution kinetics of the native gums between 40 and 90°C and 0 and 150 min revealed a steady increase in solubility of the native gums from 6.05 to 9.53 g/L (AS) and 5.90 to 8.78 g/L (AG) . The flocculation efficiency of the native AS and AG gums at 50 ppm concentration was 74.30 and 74.73%, which increased to 98.46% and 98.29% in the graft copolymerized gums, respectively.